Milk, fruit and vegetables consumption and household food security - Maryam Akbarpoor; Abdolmajid Mahdavi Damghani; Reza Deihimfard; Hadi Veisi (Payesh, 2017)
bjective (s): Food security is defined as the permanent access to sufficient, safe and nutritious food for all people in order to have an active and healthy life. To achieve sustainable food supply, quantification of food security at the household level is necessary. The main aim of this study were (i) quantitative analysis of food security in Marvdasht, Iran and (ii) Estimate the effect of milk, fruits and vegetables consumption on food security. Methods: We carried out a descriptive-survey to analyze food security status. In all 500 rural and urban households were randomly selected. The household food security was assessed by an 18-item Household Food Security questionnaire as recommended by USDA, and the correlation between variables was determined by Spearman test. Results: The results of this study showed that food insecurity in Marvdasht was 73.8 %. The findings also showed that the consumption of milk, fruit and vegetables were low. Conclusion: The study results suggest that food insecurity could be reduced with consumption of milk, fruits and vegetables.